Effect of dietary sugars on dual-species biofilms of Streptococcus mutans and Streptococcus sobrinus - a pilot study - Rosa Virginia Dutra de OLIVEIRA; Yasmin Etienne ALBUQUERQUE; Denise Madalena Palomari SPOLIDORIO; Cristiane Yumi KOGA-ITO; Elisa Maria Aparecida GIRO; Fernanda Lourenção BRIGHENTI
Abstract Introduction Frequent consumption of sugars and the presence of Streptococcus mutans and Streptococcus sobrinus are correlated with higher caries experience. Objective The aim of this pilot study was to elucidate the effect of different fermentable carbohydrates on biomass formation and acidogenicity of S. mutans and S. sobrinus biofilms. Material and method Single and dual-species biofilms of S. mutans ATCC 25175 and S. sobrinus ATCC 27607 were grown at the bottom of microtiter plates at equal concentrations for 24 h at 37 °C under micro-aerobic atmosphere. Carbohydrates were added at 2% concentration: maltose, sucrose, glucose and lactose. BHI Broth (0.2% glucose) was used as negative control. Acidogenicity was assessed by measuring the pH of spent culture medium after 24 h, immediately after refreshing the culture medium and for the next 1 h and 2 h. Crystal violet staining was used as an indicator of the total attached biofilm biomass after 24 h incubation. Data were analyzed by two-way ANOVA followed by Bonferroni post hoc test. Significance level was set at 5%. Result All carbohydrates resulted in higher biomass formation in single- and dual-species biofilms when compared to the control group. Sucrose, lactose and maltose showed higher acidogenicity than the control group in both single- and dual-species biofilms after 24 h. Conclusion These findings indicate that the type of biofilm (single- or dual-species) and the carbohydrate used may influence the amount of biomass formed and rate of pH reduction.